Cactus-inspired design principles for soft robotics based on 3D printed hydrogel-elastomer systems. (April 2021) - Bastola, Anil K.; Rodriguez, Nadia; Behl, Marc; Soffiatti, Patricia; Rowe, Nick P.; Lendlein, Andreas
Abstract: Plants have evolved many capabilities to anchor, position their stems and leaves favourably, and adapt themselves to different environmental conditions by virtue of growing. Selenicereus setaceus is a cactus and is an impressive example of a climbing plant found mostly in the Atlantic forest formations of southern Brazil. This cactus displays striking changes in stem geometry along different stages of growth: older parts are circular while the younger parts are star-like in shape. Such a transformation in shape optimizes its flexural rigidity and allows the cactus to search in three-dimensionally complex environments. Its organisation offers novel schemes for the design of plant-inspired soft robotic systems. In this paper, we have created multi-material systems for soft robotics that display controlled movements as well as mimicking the cactus stem geometries from star-like to circular. The unique star-shaped geometry is 3D printed using a soft elastomer and hydrogel is used as an actuating component. Through anisotropic swelling, the hydrogel-elastomer system adjusts its configuration and shows a controlled movement. Furthermore, the isotropic swelling of the hydrogel of the artificial cactus multi-material system result in the change in shape from star-like to circular as the cactus does naturally in the tropical forest. Graphical abstract: Unlabelled Image Highlights: Inspired by functional traits of a climbing cactus, two developmental designs (D1 and D2) are presented In D1, hydrogel-elastomer system is presented, which aims at a geometrical configuration similar to the natural cactus In D2, multi-material system is presented, which aims at a similar morphology and physical behaviour compared to the natural cactus D1 provided a controlled bending whereas D2 was capable of a shape-change from star to circlular shape upon swelling/de-swelling of the hydrogel